Unemployment and hours of work: the North Atlantic divide revisited - Pissarides, Christopher A. (London, 2006)
"I examine the dynamic evolutions of unemployment, hours of work and the service share since the war in the United States and Europe. The theoretical model brings together all three and emphasizes technological growth. Computations show that the very low unemployment in Europe in the 1960s was due to the high productivity growth associated with technological catch-up. Productivity also played a role in the dynamics of hours but a full explanation for the fast rise of service employment and the big fall in aggregate hours needs further research. Taxation has played a role but results are mixed."